A comparative study on pyrolysis characteristics of bituminous coal and low-rank coal using thermogravimetric analysis (TGA). Issue 1 (2nd January 2022) - Dwivedi, Krishna Kant; Shrivastav, Prabhansu; Karmakar, Malay Kumar; Pramanick, Achintya Kumar; Chatterjee, Pradip Kumar
ABSTRACT: This study aims to compare the pyrolysis characteristics of low-rank coal and bituminous coal with the elemental composition using thermogravimetric analysis (TGA) at the heating rates of 10, 20, 30, and 40 K/min in the temperature range 30–950°C. Friedman's method was used to find out the kinetic parameters such as activation energy and pre-exponential factor. The average value of activation energy for bituminous coal was found to be between 46.24 and 420.00 kJ/mol and for low-rank coal it was 42.321 kJ/mol. These experimental results may be useful for the utilization of low-rank coal.